A indexação temática em prontuários médicos: uma análise da literatura - Andrea Trindade Ituassu Faria (1999)
The ccmputerized-based-patient-record approacti conduce to a great necessity of representation the clinical content present in the medical records. The current systems and languages shown inadequates to represent the clinical contents, producing an important bairier on the developmento of the electronic medical records. The subject os this study is the medical recoixl and search the theoretical fundamental concepts in Tenninology to comprehend the tenminology developmet process. The purpose is to relate the major instmments of infonnation treatment and to compare the results of the studies found in the literature which object is the analysis of that languages in the treatment of the information enclosed in the medical records. The results shown that those current systems do not alow the accurate and complete representation of the clinical content, and each one shows specific deficiencies. The systems that presented the best results were respectivally: SNOMED, UMLS, Read. MeSH, ICD-9-CM, ICD-10.